Tuberculosis contact tracing in low and middle income countries: a systematic review - Azmawati Mohammed Nawi,; Norfazilah Ahmad,; Siti Norbayah Yusof,; Nurmawati Ahmad,; Zaleha Md Nor,; Juhaida Mohd Noor,; Hasanain Faisal Ghazi,; Mohammad Saffree Jeffee,; Mohd Rohaizat Hassan, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction Tuberculosis (TB) is a major global health challenge especially in low- and middle-income countries reflects improper, delayed or missed diagnosis. Contact screening should be utilized both as an efficient and effective targeted approach to intensify TB case finding. Methods Through a comprehensive systematic literature review of online database, this paper aims at providing an insight into the current practice of TB contact screening and to provide evidence based practice for formulation of appropriate policies in low- and middle-income countries. There are 24 articles included in this review from studies published from 2005 to 2014. Results Findings in literature varies substantially. Generally, contact screening is better intensified with clear operational guidelines, adequate training, include close contact outside household as appropriate and follow up at least for 1 year. Prioritizing high risk close contacts is helpful in resource limited setting. Tuberculin skin test is still of value as screening tool and intensified case finding must be accompanied with effective management protocol. Prophylaxis treatment is recommended especially for children especially less than 5 years old, unvaccinated, malnourished, living with person having HIV and close contact with MDR-TB. Conclusions Policy recommendations in improving TB management must incorporate complementary strategies to enhance case finding, effective management protocol for follow up or prophylaxis treatment, training for public health capacity and concerted dedication from various stakeholders.